Whole genome sequence analysis links chromothripsis to EGFR, MDM2, MDM4, and CDK4 amplification in glioblastoma - Furgason, John M. (Oncoscience, 2015)
BACKGROUND: Findings based on recent advances in next-generation sequence analysis suggest that, in some tumors, a single catastrophic event, termed chromothripsis, results in several simultaneous tumorigenic alterations. Previous studies have suggested that glioblastoma (GBM) may exhibit chromothripsis at a higher rate (39%) than other tumors (9%). Primary glioblastoma is an aggressive form of brain cancer that typically appears suddenly in older adults. With aggressive treatment, the median survival time is only 15 months. Their acute onset and widespread genomic instability indicates that chromothripsis may play a key role in their initiation and progression. GBMs are often characterized by EGFR amplification, CDKN2A and PTEN deletion, although approximately 20% of GBMs harbor additional amplifications in MDM2 or MDM4 with CDK4. METHODS: We used the chromothripsis prediction tool, Shatterproof, in conjunction with a custom whole genome sequence analysis pipeline in order to generate putative regions of chromothripsis. The data derived from this study was further expanded on using fluorescence in situ hybridization (FISH) analysis and susceptibility studies with colony formation assays. RESULTS: We show that primary GBMs are associated with higher chromothripsis scores and establish a link between chromothripsis and gene amplification of receptor tyrosine kinases (RTKs), as well as modulators of the TP53 and RB1 pathways. CONCLUSIONS: Utilizing a newly introduced bioinformatic tool, we provide evidence that chromothripsis is associated with the formation of amplicons containing several oncogenes involved in key pathways that are likely essential for post-chromothriptic cell survival.